2017
DOI: 10.1530/joe-17-0112
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of ELL2 induces murine prostate intraepithelial neoplasia

Abstract: Elongation factor, RNA polymerase II, 2 (ELL2) is an RNA Pol II elongation factor with functional properties similar to ELL that can interact with the prostate tumor suppressor EAF2. In the prostate, ELL2 is an androgen response gene that is up-regulated in benign prostatic hyperplasia (BPH). We recently showed that ELL2 loss could enhance prostate cancer cell proliferation and migration, and that ELL2 gene expression was down-regulated in high Gleason score prostate cancer specimens. Here, prostate-specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 53 publications
(72 reference statements)
2
35
0
Order By: Relevance
“…Previous studies suggested that ELL2 expression is regulated by androgens in prostate cancer cells . We confirmed ELL2 induction by androgens in two different prostate cancer cell lines LNCaP and C4‐2.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Previous studies suggested that ELL2 expression is regulated by androgens in prostate cancer cells . We confirmed ELL2 induction by androgens in two different prostate cancer cell lines LNCaP and C4‐2.…”
Section: Resultssupporting
confidence: 85%
“…Of these genes, 49 had a statistically significant tendency to co‐occur in tumor specimens with ELL2 alteration, while two were mutually exclusive (Table ). None of the identified AR response genes were identified previously as also being regulated by ELL2 or EAF2 . Interestingly, only SPDEF and TM4SF1 were identified as having a statistically significant tendency to co‐occur with EAF2 alteration in prostate cancer specimens (data not shown).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations